2005
DOI: 10.1016/j.ode.2004.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence that phoronids are a subtaxon of brachiopods (Brachiopoda: Phoronata) and that genetic divergence of metazoan phyla began long before the early Cambrian

Abstract: Concatenated SSU (18S) and partial LSU (28S) sequences ($2 kb) from 12 ingroup taxa, comprising 2 phoronids, 2 members of each of the craniid, discinid, and lingulid inarticulate brachiopod lineages, and 4 rhynchonellate, articulate brachiopods (2 rhynchonellides, 1 terebratulide and 1 terebratellide) were aligned with homologous sequences from 6 protostome, deuterostome and sponge outgroups (3964 sites). Regions of potentially ambiguous alignment were removed, and the resulting data (3275 sites, of which 377 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 92 publications
5
114
1
Order By: Relevance
“…The crown clade of articulated brachiopods has been recently named Neoarticulata (Carlson & Cohen 2016) for the first time, with Pan-Neoarticulata as its associated total clade (Carlson & Cohen 2016) in accordance with phylogenetic nomenclature. Results of molecular analyses support not only the monophyly of the crown clades of Brachiopoda, Inarticulata, and Neoarticulata (Figure 4) but also the monophyly of crown clade Terebratulida, Thecideida, and Rhynchonellida, and within Terebratulida, the monophyly of crown clade Terebratellidina and Terebratulidina (Cohen & Gawthrop 1997;Cohen 2000Cohen , 2007Cohen , 2013Cohen & Weydmann 2005). Total clade monophyly has not been established for most of these groups, however.…”
Section: Phylogenymentioning
confidence: 91%
“…The crown clade of articulated brachiopods has been recently named Neoarticulata (Carlson & Cohen 2016) for the first time, with Pan-Neoarticulata as its associated total clade (Carlson & Cohen 2016) in accordance with phylogenetic nomenclature. Results of molecular analyses support not only the monophyly of the crown clades of Brachiopoda, Inarticulata, and Neoarticulata (Figure 4) but also the monophyly of crown clade Terebratulida, Thecideida, and Rhynchonellida, and within Terebratulida, the monophyly of crown clade Terebratellidina and Terebratulidina (Cohen & Gawthrop 1997;Cohen 2000Cohen , 2007Cohen , 2013Cohen & Weydmann 2005). Total clade monophyly has not been established for most of these groups, however.…”
Section: Phylogenymentioning
confidence: 91%
“…This gave a phylum with three closely related subphyla, Linguliformea, Craniiformea, and Phoroniformea, that made up one major clade and the Rhynchonelliformea that made up the other major clade. Subsequent work by Cohen and Weydmann (2005) using both the small subunit and partial large subunits of rDNA sequences showed that the Phoroniformea were the basal members of its clade and that the Linguliformea and Craniiformea were the derived members of that clade (Fig. 1B).…”
Section: The Fossil Record and Phylogenetics Of Brachiopodsmentioning
confidence: 96%
“…For extant genera, the time when the order they belong to first appeared and any earlier orders that gave rise to the order they reside in are indicated (adapted from Williams et al, 1996). B) Molecular phylogeny for extant brachiopod subphyla based on the small subunit of rDNA and partial large subunits of rDNA (adapted from Cohen and Weydmann, 2005). the outgroup for the cladistic classification, nested with the Linguliformea and Craniiformea within the phylum Brachiopoda (see Halanych, 2004 for a discussion of earlier work on the phylogenetic affinities of the Phoronida).…”
Section: The Fossil Record and Phylogenetics Of Brachiopodsmentioning
confidence: 99%
“…The more divergent morphologies present within the Lophotrochozoa confound traditional evolutionary interpretations of many larval and adult characters, especially with regard to the "lophophorates." More recent studies on the development and larval anatomy of phoronids and brachiopods have expanded our understanding of their evolutionary affinities (Santagata and Zimmer, 2002;Santagata, 2004b;Cohen and Weydmann, 2005). However, often left anatomically and phylogenetically orphaned by these reports, are the bryozoans.…”
Section: Introductionmentioning
confidence: 99%